PENGARUH TEORI SLAVIN TERHADAP PEROLEHAN BELAJAR PESERTA DIDIK KELAS V SDS MUJAHIDIN PONTIANAK - Yuniarti, Retno; Sabri, Tahmid; Yuniarti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This research aims to understand the influence of the use of a Teory Slavin Team Assisted Individulization of the results of the learning social science a student of class v sds Mujahidin south Pontianak.Population in this research is all students grade V academic year 2016 / 2017 which consisted of 168 people.Sample in this research were students grade 5 which consisted of 168 people consisting of 35 the VB and 35 the V A ( class eksperimen).Instrument gatherer data of student learning the test results obtained from pre test and post test. The results of the study , obtained the average test results final grade control 60,78 and the average test results final grade 74,49 experiments obtained thitung of 3,8403 and ttabel with Î± = 5% and dk = 68 as much as , which means thitung (3,8403) > ttabel (1,9974), thus then Ha accepted .Of reckoning as effect size (ES), obtained ice as much as 0,93 ( criteria high ) .This means that learning with the use of the kind of classroom Teory Slavin Team Assisted Individualization a difference that high evaluation learning outcomes from the classroom v of public elementary school Mujahidin .Â Keyword : Influence, Learning TeorySlavin, Study Result, Civit EducationÂ